Peran Ruang Baca Rimba Bulan dalam Meningkatkan Kemampuan Literasi Masyarakat Kota Padang Panjang - Wahyuni, Sri; Safri, T Mulkan (Jurnal Adabiya, 2023)
The presence of a Community Reading Park in the midst of the community is an alternative to increasing the literacy skills of the community and building interest in reading through reading materials and available programs aimed at educating the nation's children. The research aims to see how far the role of the Rimba Bulan Reading Room goes in developing people's reading interests and literacy skills. The type of research used is qualitative research with a descriptive approach. Collecting data using observation, interviews, and documentation The data source is primary data obtained from interviews with TBM managers in the Rimba Bulan Reading Room. Furthermore, the data is processed to test the validity of the data using source triangulation. The results of the study show that the Rimba Bulan Reading Room in Padang Panjang City plays a very important role in developing community literacy with various program activities that have been carried out by involving children and adolescents to read books, participate in programs that TBM carries out such as drawing, reading poetry, playing traditional music, teaching mothers in waste management to become workers, and so on, to improve the economy.